Knowledge and attitude toward transcranial magnetic stimulation among rehabilitation specialists in Saudi Arabia - Albishi, Alaa M.; Alhadlaq, Saja A.; Altowairqi, Rahaf T.; Alharbi, Mohammed F.; Alsubiheen, Abdulrahman M.; Alosaimi, Manal H.; Bashir, Shahid; Alokaily, Ahmad O. (Frontiers in Bioengineering and Biotechnology, 2024)
Research has demonstrated the benefits of transcranial magnetic stimulation (TMS) in rehabilitation. TMS has been widely used in clinical and research settings for individuals with and without neurological dysfunctions. Therefore, understanding the knowledge and attitudes of rehabilitation specialists regarding TMS is crucial for its application. To our knowledge, no such studies have previously been conducted in the rehabilitation field. Therefore, this study is the first to assess rehabilitation specialists' knowledge of and attitudes toward TMS. An observational cross-sectional study using a self-administered online survey was conducted among 102 rehabilitation specialists to assess their knowledge and attitudes regarding TMS application in rehabilitation sciences. Descriptive and inferential statistics were used to describe the knowledge and attitudes of rehabilitation specialists toward TMS and examine the impact of different factors such as gender, education level, acceptability, and practice on these outcomes. Rehabilitation specialists who participated in this study showed a limited level of general knowledge of TMS in rehabilitation (7.81 ± 6.20, 37.19%). However, a significant association between educational levels and knowledge was found. Higher knowledge scores were observed for specialists with post-graduate degrees compared to those with only a bachelor's degree. Moreover, knowledge level, experience, and availability of TMS equipment in the workplace led to a positive attitude toward TMS among rehabilitation specialists. A low knowledge level among rehabilitation specialists was attributed to their level of education. Nevertheless, specialists showed an overall positive attitude toward TMS. Therefore, customized medical education is necessary to incorporate TMS theory and applications into neuroscience and rehabilitation courses for rehabilitation specialists as it holds significant promise as a therapeutic tool.1.